2006
DOI: 10.1080/08039480500504982
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of mental health and quality of life in male tortured refugees

Abstract: Some of the most frequently reported mental health problems in traumatized refugees are depression, anxiety and post-traumatic stress disorder (PTSD). The aim of this paper is to describe a group of tortured refugees referred to the Rehabilitation and Research Centre for Torture Victims (RCT) and to study the importance of past trauma/torture and post-migratory factors for the present symptoms of PTSD, depression, anxiety and for health-related quality of life. The sample comprises 63 male tortured refugees ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
88
1
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(96 citation statements)
references
References 38 publications
6
88
1
1
Order By: Relevance
“…Phases II and III should focus on the patient's priorities, which may include social integration and/or treatment of symptoms. Unemployment, isolation and discrimination may overshadow the efficacy of mental health treatment in many patients, 430 which suggests that multifaceted interventions that include primary care, community organizations and other social institutions may be effective. 432 …”
Section: Clinical Considerationsmentioning
confidence: 99%
See 2 more Smart Citations
“…Phases II and III should focus on the patient's priorities, which may include social integration and/or treatment of symptoms. Unemployment, isolation and discrimination may overshadow the efficacy of mental health treatment in many patients, 430 which suggests that multifaceted interventions that include primary care, community organizations and other social institutions may be effective. 432 …”
Section: Clinical Considerationsmentioning
confidence: 99%
“…51 Studies of child refugees report 11% prevalence of posttraumatic stress disorder. 429,430 Symptoms may be reactivated when faced with new traumas, particularly if reminiscent of earlier traumatic experiences. 431 Torture and cumulative trauma are the strongest predictors of post-traumatic stress disorder and are associated with chronic physical and mental health problems.…”
Section: What Is the Burden Of Illness Of Posttraumatic Stress Disordmentioning
confidence: 99%
See 1 more Smart Citation
“…Rather, the study found social factors to be significant contributors to the subjects' symptomatology versus the impact of torture per se. Drawing on another study with similar treatment outcomes (Miller et al, 2002), Carlsson, Mortensen, & Kastrup (2006) argue for a broader scope in treatment interventions that are more closely linked to the context in which refugees live.…”
mentioning
confidence: 99%
“…3 A number of studies have investigated the link between pain and PTSD, including amongst torture survivors specifically. 4 Chronic pain is highly prevalent in torture survivors, 4 often co-occurs with PTSD and is associated with poorer prognosis.…”
Section: Introductionmentioning
confidence: 99%